Direct Inhibition of the Allergic Effector Response by Raw Cow’s Milk—An Extensive In Vitro Assessment - Suzanne Abbring (Cells, 2020)
The mechanisms underlying the allergy-protective effects of raw cow’s milk are poorly understood. The current focus is mainly on the modulation of T cell responses. In the present study, we investigated whether raw cow’s milk can also directly inhibit mast cells, the key effector cells in IgE-mediated allergic responses. Primary murine bone marrow-derived mast cells (BMMC) and peritoneal mast cells (PMC), were incubated with raw milk, heated raw milk, or shop milk, prior to IgE-mediated activation. The effects on mast cell activation and underlying signaling events were assessed. Raw milk was furthermore fractionated based on molecular size and obtained fractions were tested for their capacity to reduce IgE-mediated mast cell activation. Coincubation of BMMC and PMC with raw milk prior to activation reduced β-hexosaminidase release and IL-6 and IL-13 production, while heated raw milk or shop milk had no effect. The reduced mast cell activation coincided with a reduced intracellular calcium influx. In addition, SYK and ERK phosphorylation levels, both downstream signaling events of the FcεRI, were lower in raw milk-treated BMMC compared to control BMMC, although differences did not reach full significance. Raw milk-treated BMMC furthermore retained membrane-bound IgE expression after allergen stimulation. Raw milk fractionation showed that the heat-sensitive raw milk components responsible for the reduced mast cell activation are likely to have a molecular weight of > 37 kDa. The present study demonstrates that raw cow’s milk can also directly affect mast cell activation. These results extend the current knowledge on mechanisms via which raw cow’s milk prevents allergic diseases, which is crucial for the development of new, microbiologically safe, nutritional strategies to reduce allergic diseases.